2007
DOI: 10.1653/0015-4040(2007)90[502:poadeo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of Artificial Diet: Effects of Composition and Size of Prey and Diet Domes on Egg Production by Orius Insidiosus (Heteroptera: Anthocoridae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Ferkovich et al (2007) found that E. kuehniella eggs had the highest protein concentrations among five Lepidoptera species tested. It is also possible that the fat content is higher in E. kuehniella eggs than in other prey, which could contribute to the greater development rate and reproduction on that diet (De Clercq et al 2005).…”
Section: Discussionmentioning
confidence: 90%
“…Ferkovich et al (2007) found that E. kuehniella eggs had the highest protein concentrations among five Lepidoptera species tested. It is also possible that the fat content is higher in E. kuehniella eggs than in other prey, which could contribute to the greater development rate and reproduction on that diet (De Clercq et al 2005).…”
Section: Discussionmentioning
confidence: 90%
“…Unfortunately, oviposition was significantly reduced in females fed the supplemented artificial diet rather than E. kuehniella eggs. Similarly, O. insidiosus oviposition was enhanced when artificial diet (in 25 and 50 ll hemispherical capsules or domes) was supplemented with protein from E. kuehniella eggs in comparison to unmodified artificial diet (Ferkovich et al 2007). Nevertheless, oviposition rate was greatest and mortality was least when females were fed whole E. kuehniella eggs.…”
Section: Benefits and Limitations Of Artificial Diets Containing Insementioning
confidence: 96%
“…High pupa survival of E. connexa, in all treatments, suggests that prey tested supplied the metabolic needs of this predator in the previous stages. This is important because prey type affects fertility and other biological features of predators (Ferkovich et al, 2007).…”
Section: Treatments Prepupamentioning
confidence: 99%
“…Polyphagous feeding habits of Eriopis connexa (Germar) (Coleoptera: Coccinellidae) have been reported (Miller and Paustian, 1992;Miller, 1995;Sarmento et al, 2004Sarmento et al, , 2007Silva et al, 2009), suggesting that this predator can feed on a wide number of insect pests of corn and sorghum, but food availability and sustainability are fundamental for establishing a species in a new area (Eubanks and Denno, 2000;Roger et al, 2000;Soares et al, 2004;Berkvens et al, 2008).…”
Section: Introductionmentioning
confidence: 99%